KOMUNIKASI PEMASARAN DI INSTAGRAM PADA MASA PANDEMI COVID-19 DALAM MENINGKATKAN BRAND AWARENESS THE MAYFLOWER JAKARTA 2021: - Atmojo, Heri; Nabillah, Tasya (JURNAL PARIWISATA VOKASI, 2023)
The Mayflower Jakarta utilizes social media, especially Instagram, in communicating its marketing to build brand awareness and get positive responses from consumers. Therefore, researchers want to know how marketing communication activities on Instagram during the Covid- 19 pandemic have built brand awareness for The Mayflower Jakarta 2021. The method used in this research uses a qualitative descriptive method and a post-positivism paradigm. Primary research data was obtained through in-depth interviews with internal parties of The Mayflower Jakarta. Meanwhile, secondary data through Instagram observations and documentation. Communication activities via Instagram at The Mayflower Jakarta in conducting a planning, implementation and evaluation process. The planning process carried out is endorsment with KOL (Key Opinion Leader). Then the implementation process is carried out by providing information in the form of content and promos. Then, in the evaluation process that was carried out, it was found that the followers of The Mayflower Jakarta, the views obtained were 7,982 and the total likes were 1,200 and comments 3,131.